2015
DOI: 10.1113/jp270229
|View full text |Cite
|
Sign up to set email alerts
|

The TRPV1 channel in rodents is a major target for antinociceptive effect of the probiotic Lactobacillus reuteri DSM 17938

Abstract: Key pointsr Certain probiotic bacteria have been shown to reduce distension-dependent gut pain, but the mechanisms involved remain obscure.r Live luminal Lactobacillus reuteri (DSM 17938) and its conditioned medium dose dependently reduced jejunal spinal nerve firing evoked by distension or capsaicin, and 80% of this response was blocked by a specific TRPV1 channel antagonist or in TRPV1 knockout mice.r The specificity of DSM action on TRPV1 was further confirmed by its inhibition of capsaicin-induced intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 76 publications
1
82
0
Order By: Relevance
“…Lastly, Perez‐Burgos et al . () have reported that the administration of L. johnsonii to jejunum had reduced the firing rate of vagal afferent fibres in ex vivo jejunal segment mesenteric nerve recording preparation. It is assumed that changing the firing rate of VN can induce secretions of serotonin, GABA, and glutamate in the brain, but since there is no an in vivo study, it is still hypothetical.…”
Section: The Modification Of Vagal Afferent Fibresmentioning
confidence: 97%
“…Lastly, Perez‐Burgos et al . () have reported that the administration of L. johnsonii to jejunum had reduced the firing rate of vagal afferent fibres in ex vivo jejunal segment mesenteric nerve recording preparation. It is assumed that changing the firing rate of VN can induce secretions of serotonin, GABA, and glutamate in the brain, but since there is no an in vivo study, it is still hypothetical.…”
Section: The Modification Of Vagal Afferent Fibresmentioning
confidence: 97%
“…[69] Bacterial modulation of spinal cord responses has been demonstrated using probiotic species; the presence of live Lactobacillus reuteri reduces spinal nerve firing in response to the introduction of painful visceral stimulation. [70] …”
Section: Spinal Cord Transmission Of Microbiota To Amygdala Signalsmentioning
confidence: 99%
“…We have been extensively involved in studies of the effects of the gut microbiota on the functions of the enteric nervous system and brain including behaviour (Bienenstock et al ., ; Perez‐Burgos et al ., ; Forsythe et al ., ). This field has become known as the gut–brain axis or the microbiota–gut–brain axis.…”
Section: General Commentarymentioning
confidence: 98%